Analisis Undang-Undang Nomor 31 Tahun 1999 Tentang Korupsi Dalam Perspektif Hukum Islam - Muh. Kurniawan BW; Aditya Fajri Kurnia Pradana; Yahya Ibadu Rahman; Salman Alfarisi (Asy-Syari’ah : Jurnal Hukum Islam, 2023)
Corruption can be defined as the behavior of individuals who use the authority and position for personal gain, and cause harm and the public interest. Real form of corrupt behavior can manifest fraud, bribery, financial and administrative data manipulation other similar actions. Corruption in Indonesia has become a chronic problem that is very sad. Such as disease, corruption has spread widely throughout the country with a number from year to year tend to increase as well as the various modes. The government then issued Law no. 20 of Law No. 2001 on the amendment. 31 of 1999. The law imposed criminal sanctions for perpetrators of acts of corruption. Threats of light with the heaviest penalty death penalty. Criminal death then caused polemics in various circles. Measuring corruption is not only seen in its social context, but also in the context of the self and the individual human being. Islam emphasizes that corruption is a kind of denial that such action should be eliminated from society. Islam also understand the corruption is not only seen from the legal aspects, but also of the socio-cultural aspects, psychologial, and beliefs. From the Islamic point of view, a person arrested for corruption convicted. In addition, Islam also recognizes a concept called the ta'zir, it is the authority given to a person or body to carry out the policy of criminalization to cases in which the Qur'an and Sunnah are not clearly set Keywords: Corruption, Islamic law, analysis